Kitab Carita Anis Sahabat Rasulullah Kajian atas Naskah Sunda Islami - I. Syarif Hidayat (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2012)
Islamic Sundanese manuscripts are part of Nusantara manuscripts. Among the manuscripts that describe the history of prominent religious figures in the era of Prophet Muhammad is a manuscript of Kitab Carita Anis Sahabat Rasulullah (KCASR). The manuscript depicts two Prophet Muhammad’s companions with contradictory characters of greediness and selfishness, on the one hand, and of humbleness and piety, on the other. The manuscript is an adaptation of Tha’labah narrative, a popular story that contains religious teaching and is usually presented in personality development trainings for current Muslim community